Grammatical Metaphor in English Textbook of Junior High School - Purnama Rika Perdana; Amrin Saragih; Sumarsih Sumarsih (LINGUISTIK TERAPAN, 2015)
This study investigates grammatical metaphor in the English textbook of Junior High School. The objectives of the study are to identify what grammatical metaphor are used in Junior High School English textbook, to describe the way those grammatical metaphor are used, and to explain the reason why the English textbook of Junior High School uses those grammatical metaphors. The research was conducted by applying descriptive qualitative design. The data for this study were texts taken from an English textbook for Junior High School. The data were collected by selecting the texts based on their subjects, then retyping the passage of the text, editing the passage by breaking down the clauses into a data, and printing out the data. The findings of the study show that there are five grammatical metaphors used in the English textbook, namely the realization of epithet = thing, event = thing, event = epithet, head = modifier, and manner = epithet. It is found that the reason why the English textbook uses the grammatical metaphors is in order to make the information compact or denser which directs the students to a scientific writing model mostly applied in their higher educational level. Keywords: grammatical metaphor, English textbook, Junior High School